PENGARUH IKLAN INFLUENCER DAN FITUR LIVE STREAMING TERHADAP MINAT BELI KONSUMEN BITTERSWEET BY NAJLA - Riska Dea Putri; Dhiwa Harum Setyawan; Rahmat Abdullah Putra; Husnul Khatimah (Taksasila Edukasi Insani, 2023)
In today's digital age, social media has become a popular platformfor promoting products and services. One of the increasinglypopular platforms is TikTok, which has become a favorite livestreaming platform for users around the world. On the other hand,influencer advertising has become one of the effective marketingstrategies to attract consumer attention. This research uses aquantitative approach with primary data obtained from distributingquestionnaires. The research scale used in the questionnaire is aLikert scale. The questionnaire distribution used purposivesampling technique. Respondents in this study are consumers ofBittersweat By Najla and live in Bekasi. The effect of InfluencerAdvertising on buying interest has a positive and significant effecton consumer buying interest in Bittersweet by Najla because the tvalue is greater than the t table (3.527 1.988). And the effect ofLive Streaming on buying interest has a positive and significanteffect on consumer buying interest in Bittersweet by Najla becausethe t value is greater than the t table (7.322 1.988). Based onresearch conducted on the influence of influencer advertising andTikTok's live streaming feature on consumer buying interest inBittersweet by Najla, it can be concluded that these two factors havea positive and significant influence on consumer buying interest.Keywords : Influencer, Live Streaming, willingness to buy